2020
DOI: 10.7759/cureus.9207
|View full text |Cite
|
Sign up to set email alerts
|

A Mother's Cry: A Race to Eliminate the Influence of Racial Disparities on Maternal Morbidity and Mortality Rates Among Black Women in America

Abstract: Racial/ethnic disparities in maternal care exist, even as medicine continues to progress on several aspects, medical care continues to fail countless women each year, particularly minority women and women of color. Black and American Indian/Alaska Native women experienced exponentially more pregnancy-related deaths. Recognizing factors that underlie disparities in pregnancy-related deaths and implementing preventive approaches to resolve them may mitigate racial/ethnic disparities in pregnancy-related mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It is possible that the differences in prenatal substance use screening by payor type and other individuallevel characteristics like race, marital status, or age are influenced by provider biases, which manifest in inequitable decision-making based on who a provider deems most likely to use substances. 32 Our results also reveal that some variation in screening may be related state policy environment. Finally, we find that health system-level level factors, such as differences in protocols in sites that serve a greater portion of privately insured individuals, like private practices, 33 may also contribute to the variation in screening revealed in our study.…”
Section: Discussionmentioning
confidence: 52%
“…It is possible that the differences in prenatal substance use screening by payor type and other individuallevel characteristics like race, marital status, or age are influenced by provider biases, which manifest in inequitable decision-making based on who a provider deems most likely to use substances. 32 Our results also reveal that some variation in screening may be related state policy environment. Finally, we find that health system-level level factors, such as differences in protocols in sites that serve a greater portion of privately insured individuals, like private practices, 33 may also contribute to the variation in screening revealed in our study.…”
Section: Discussionmentioning
confidence: 52%
“…Due to long standing blatant and, more recently, neutrally written policies in the US (Sivashanker et al 2020 ; Historical Foundations of Race n.d. ; Rothstein 2017 ; Anderson 2018 ; Hajnal et al 2017 ; Powell 2014 ), Black and Brown people traditionally have less access to care (Flower et al 2020 ), opportunity, access to greenspaces (Bruton and Floyd 2014 ; Engelberg et al 2016 ; Browning and Rigolon 2018 ), and other resources such as well funded schools (Darling-Hammond 2007 ; Morgan and Amerikaner 2018 ). They face discrimination in their interactions with law enforcement (Schwartz 2020 ; Graham et al 2020 ; Bor et al 2018 ; Edwards et al 2018 ; Alang 2018 ) and the health system (Egede 2006 ; Alang et al 2020 ; Sakran et al 2020 ; Institutional Racism in the Health Care System n.d. ; Keshavan 2020 ; Evans et al 2020 ; Oribhabor et al 2020 ). Generational deficiencies have compounded to form the basis of current health system interactions and outcomes.…”
Section: Mainmentioning
confidence: 99%
“…Researchers have often speculated that the striking disparities among non-Hispanic Black women are due to higher rates of comorbidities including obesity, chronic hypertension, and diabetes mellitus (Ananth et al, 2019;Fasanya et al, 2021). However, many studies have controlled for comorbidities and socioeconomic status and nd that the disparities remain (Marshall et al, 2014;Oribhabor et al, 2020;Tanaka et al, 2007). Race is a social construct meant to subjugate certain groups in the context of white supremacy and not a biological one, thus there has been a focus shift to social determinants of health in explaining the disparities in maternal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Race is a social construct meant to subjugate certain groups in the context of white supremacy and not a biological one, thus there has been a focus shift to social determinants of health in explaining the disparities in maternal mortality. In addition to socioeconomic status, studies have suggested that factors like geographic location, access to prenatal care, quality of hospitals patients attend, medical gaslighting or psychosocial factors are reasons for the racial disparities in maternal mortality rate in the US (Christian et al, 2021;Hu et al, 2019;Oribhabor et al, 2020;Tanaka et al, 2007). Psychosocial factors are particular of interest in the context of hypertension in pregnancy, since stress can impart biological changes to the body, and is associated with hypertension development (Spruill, 2010).…”
Section: Introductionmentioning
confidence: 99%